Analisis Pengaruh Likuiditas, Profitabilitas, dan Pertumbuhan Penjualan Terhadap Kebijakan Dividen pada Perusahaan Farmasi di Bursa Efek Indonesia (2020-2023) - Agusmadi Agusmadi; Nurfarida Nurfarida; Azlim Azlim; Riza Ul Fahmi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The effect of liquidity, profitability and sales growth on dividend policy (empirical study of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2023 period). Based on the analysis of financial statement information, investors can find out the comparison between the intrinsic value of shares compared to the market price of the shares of the company concerned and on this comparison investors will be able to make decisions to buy or sell the shares concerned. The sample of this study is 12 pharmaceutical companies listed on the Indonesia Stock Exchange in 2020-2023 by taking financial data for 4 (four) years so that it will produce 48 data. Data collection using secondary data in this study is data on profitability, liquidity and sales growth affecting dividend policy in pharmaceutical sub-sector manufacturing industry companies listed on the Indonesia Stock Exchange. Data analysis to see the influence of bound variables and independent variables using multi-variable linear regression equation analysis. Test the hypothesis using the ttest statistical test, with the help of the computer program SPSS V.24.0 For windows with a signification level of 5%. Based on the results of the study: Partially, liquidity has a significant effect on dividend policy. (2) partial profitability has a significant effect on dividend policy. (3) partial profitability has a significant effect on the dividend policy for pharmaceutical companies listed on the Indonesia Stock Exchange in 2020-2023. R square of 0.0766 means Liquidity, Profitability, and Company Growth, giving a joint influence of around 76.6% on Dividend Policy, while the remaining 24.4% is influenced by other variables.